Breast Cancer A New Era in Management - Francescatti, Darius S.; Silverstein, Melvin J. (Springer New York : Imprint: Springer, 2014)
Breast Cancer: A New Era in Management provides a compendium of succinct analysis of the many facets involved in the present day management of the breast cancer patient.  The text provides the clinician or student with basic foundational knowledge in the rapidly expanding areas of expertise that are required for both the diagnosis and treatment of the breast cancer patient.  Each topic, whether diagnostic or therapeutic, is presented in a straightforward fashion incorporating as part of each topic a description of the historical clinical landmarks leading to the present day, their present day position in the care of the breast patient, and finally, an assessment of possible future application and adaptation in clinical practice.  Emphasis is placed on clear and concise explanations of each topic presented in stepwise fashion from fundamental elements to the more complex. Breast Cancer: A New Era in Management will act as a ready reference for the practicing surgeon and students seeking practical information on a particular clinical topic or scenario.